Fast Adsorption of Soft Hydrogel Microspheres on Solid Surfaces in Aqueous Solution. Issue 40 (25th August 2017) - Matsui, Shusuke; Kureha, Takuma; Hiroshige, Seina; Shibata, Mikihiro; Uchihashi, Takayuki; Suzuki, Daisuke
Abstract: The real‐time adsorption behavior of polymeric colloidal microspheres onto solid surfaces in aqueous solution was visualized for the first time using high‐speed atomic force microscopy (HS‐AFM) to reveal how the softness of the microspheres affects their dynamic adsorption. Studies that focus on the deformability of microspheres upon dynamic adsorption have not yet been reported, most likely on account of a lack of techniques that appropriately depict the dynamic adsorption and deformation behavior of individual microspheres at the nanoscale in real time. In this study, the deformability of microspheres plays a crucial role on the adsorption kinetics, that is, soft hydrogel microspheres adsorb faster than harder elastomeric or rigid microspheres. These results should provide insight towards development of new colloidal nanomaterials that exhibit effective adsorption on specific sites in aqueous solution. Abstract : A soft landing : The detailed adsorption and deformation kinetics of polymeric colloidal microspheres on solid surfaces in aqueous solution under flow conditions were examined by high‐speed atomic force microscopy (HS‐AFM). The elasticity (deformability) of the microspheres crucially affects their adsorption kinetics.